(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
Relevance of the topic. Every year the number of dental implants installed by dental surgeons and maxillofacial surgeons is steadily growing. One of the contraindications indicating the impossibility of installing a dental implant in patients.The presence of a severe degree of alveolar bone atrophy in a patient, which sharply limits the possibility of dental implantation, often occurs with tooth loss. Currently, there is an active search for prerequisites for expanding the indications for dental implantation surgery, for which various surgical techniques are recommended to increase the volume of alveolar bone tissue. Unfortunately, even today the problem of choosing methods and materials for increasing the volume of alveolar bone tissue of the jaws has not been fully resolved, taking into account the features of the regenerative processes of the alveolar bone when increasing its volume, anatomical and structural features of bone tissue in a specific clinical situation.